Challenges affecting physically disadvantaged users in accessing library services in polytechnical colleges - Chibangwa, Pretty; Chigwada, Josiline (Journal of access services, 2025)
Physical differences are part of human life, some are physically disadvantaged while others physically advantaged. According to information from World Health Organization (WHO), 15% of the world's population has some kind of disability, which in numbers represents more than one billion people. Yet all should have equal opportunities and access to resources despite these differences. Libraries are not an exception in providing equal opportunities in service provision to all whether advantaged or disadvantaged. According to the regulatory and legal framework including the UNESCO Manifesto, United Nations Convention on the Rights of Persons with Disability, laws on libraries and accessibility of different IFLA members, and other protocols, library services should be provided on the basis of equal access to everyone. This paper focused on the challenges affecting physically disadvantaged users in accessing library services in polytechnics and how these libraries have responded to inclusivity in terms of service delivery. Particular reference was given to one polytechnic. A mixed method approach was used with a sample of 180 respondents that was purposively selected for the study. Structured questionnaires and semi-structured interviews were used to generate data. Findings revealed that the library was lagging behind in offering inclusive services that offer equal opportunities to all users despite physical differences. This has resulted in discrimination on service delivery. The paper recommended library policies on inclusivity and practical implementation, establishment of disability resource centers, as well as a holistic approach from decision makers of the polytechnic and parent ministry to improve service delivery on the physically disadvantaged users.